Immune system modulation produced by ultraviolet radiation - Cela, Eliana Maiten (2018)
Exposure to ultraviolet radiation (UVr) contained in sunlight is a major cause of skin illness, such as sunburn, aging and cancer. UVr triggers local effects on the skin, which involve local inflammation, tissue remodel, regulatory cytokines release and migration of dendritic cells (DCs). However, these localized effects on the exposed area are not the only ones that take place after sun or UVr exposure. A less known effect of UVr is the modulation of systemic immunity, through the generation of specific regulatory cells. These cells are induced, at least in part, by skin-migrating tolerogenic DCs. Moreover, bone marrow cell precursors can also be biased to a tolerogenic or suppressor phenotype.The sunlight or UVr-induced immune system modulation can cause skin disorders, like skin cancer and cutaneous photosensitivity in Lupus, but it also may be useful to treat cutaneous pathologies, such as psoriasis and vitiligo. Moreover, the systemic immunosuppressor effect of UVr-exposure may also be useful to treat autoimmunity of internal organs. Finally, as an inducer of cutaneous inflammatory response, UV phototherapy may also be useful in the treatment of cutaneous infections.Overall, UVr has profound immunomodulatory capacity that can be useful or deleterious for human health.